2002
DOI: 10.1038/sj.bjc.6600476
|View full text |Cite
|
Sign up to set email alerts
|

The bisphosphonate pamidronate induces apoptosis in human melanoma cells in vitro

Abstract: Pamidronate belongs to the class of nitrogen-containing bisphosphonates that are potent inhibitors of bone resorption frequently used for the treatment of osteoporosis and cancer-induced osteolysis. The inhibition of osteoclasts' growth has been suggested as the main mechanism of the inhibitory effect of pamidronate on bone metastases. Recent findings indicated that bisphosphonates also have a direct apoptotic effect on other types of tumour cells. Nitrogen-containing bisphosphonates were shown to inhibit farn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 29 publications
3
46
0
Order By: Relevance
“…This proapoptotic ability of BPs has been strongly correlated with the specific antiresorptive potency of each compound. Specifically, it has been demonstrated that ZOL has a direct effect on human multiple myeloma (Shipman et al, 1997), breast cancer (Senaratne et al, 2000), prostate cancer (Lee et al, 2001) and melanoma cells (Riebeling et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This proapoptotic ability of BPs has been strongly correlated with the specific antiresorptive potency of each compound. Specifically, it has been demonstrated that ZOL has a direct effect on human multiple myeloma (Shipman et al, 1997), breast cancer (Senaratne et al, 2000), prostate cancer (Lee et al, 2001) and melanoma cells (Riebeling et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…To ensure cell viability during prolonged incubation of metformin in serum-free medium, cell viability was assessed with the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay performed according to the manufacturer's suggestions (Sigma). In addition, cytotoxicity was assessed by measuring lactate dehydrogenase release into the culture medium using the cytotoxicity detection kit (Roche Applied Science) as described previously (26). Under the conditions of our studies, treatment of HepG2 cells with metformin had no detectable cell toxicity.…”
Section: Materials-metforminmentioning
confidence: 99%
“…Furthermore, zoledronic acid has shown synergistic induction of cancer cell apoptosis in vitro when combined with a variety of agents, e.g., with imatinib mesylate in leukemia cells 19 or in lung cancer cells, 20 with gemcitabine in prostate cancer cells, 21 with paclitaxel or tamoxifen 22,23 or tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) 24 in breast cancer cells and with dexamethasone in myeloma cells. 25 Other bisphosphonates investigated for synergistic cell death in combination with chemotherapeutic agents have shown either no effect (pamidronate with DTIC in melanoma cell lines) 26 or additive activity at best (ibandronate with taxanes in breast cancer cells). 27 Anthracyclines such as doxorubicin and epirubicin are commonly used to manage early and metastatic breast cancer.…”
mentioning
confidence: 99%